Disruptive Domesticity in Shakespearean Drama - Turi, Zita (Hungarian Journal of English and American Studies, 2021)
Book review: Whipday, Emma. Shakespeare’s Domestic Tragedies: Violence in the Early Modern Home. Cambridge: Cambridge UP, 2019. 262 pages. ISBN 9781108474030. Pbk. £29.99